A reconfiguração da campanha eleitoral na era da tecnicidade: a propaganda televisiva no Brasil e no México em 2006 - Daniela Paiva de Almeida Pacheco (2010)
The following work focuses on the study of communication strategies that give unity and identity to television advertisements aimed at the presidential election by the three parties (or coalitions) that performed better in the polls in 2006, in Brazil and Mexico. The analysis are carried out having in mind the discussion on the transformation of the technical dimension of politics, understood as the historical moment and the environment in which actors both parties and candidates - struggle. The choice of this theoretical approach was only possible after the review of the key assumptions presented by the literature on the changes detected in the forms of election campaigning in different democracies, in recent decades. According to the literature, certain factors have influenced the electioneering. Those factors defined the interest in comparing the advertisements of the listed countries, since Brazil and Mexico have different electoral systems, contest rules and partidary dynamics. Changes in communications strategies are analyzed from three dimensions - (i) role of the actor, (II) propositional character; (III) speech focused on the competence of management. Each dimension represents an analytical category and to each are set indicators. The work considers the realm of electoral advertisements, regardless of time and format of these; accordingly in Brazil both programs reported on Schedule Advertising Free Elections (HGPE) and the spots are studied, placed along the normal programming of broadcasters television, referring to the first turn. In Mexico, the dominant format is the spot known as "promotional." Overall, we analyze 339 electoral advertisements, which amounts to nearly eight hours of recording. The work researches advertisements of the coalitions A Força do Povo (PT/PRB/PCdoB), Por um Brasil Decente (PSDB/PFL) e Frente de Esquerda (PSOL/PSTU/PCB), no Brasil; do PAN e das coligações Alianza por México (PRI/PVEM) e Por el Bien de Todos (PRD/PT/Convergencia), no México.